2014
DOI: 10.4103/1658-354x.140867
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral impact of sickle cell disease in young children with repeated hospitalization

Abstract: Background:Sickle cell disease (SCD) in children with a history of repeated hospitalization is distressing for children as well as their parents leading to anxiety and has negative effects on the psychological state of children and their families. Objective: The aim of the study was to determine the overall effect of SCD on the behavior of young children age 1½ to 5 years old who had repeated history of hospitalization, compared to a control group of healthy children attended a vaccination clinic.Patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…Other research has found a relationship between pain and psychiatric disorder, and has demonstrated that reduced pain is associated with significant improvements in general health, quality of life, and mood disorder in SC patients (3,15). Bakri et al (10) found that patients with SCD and who had history of repeated hospitalization are at an increased risk of developing behavioral problems and psychiatric disorders, including depression and anxiety. That study reported that psychological counseling, social support, and proper pain management may minimize these consequences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other research has found a relationship between pain and psychiatric disorder, and has demonstrated that reduced pain is associated with significant improvements in general health, quality of life, and mood disorder in SC patients (3,15). Bakri et al (10) found that patients with SCD and who had history of repeated hospitalization are at an increased risk of developing behavioral problems and psychiatric disorders, including depression and anxiety. That study reported that psychological counseling, social support, and proper pain management may minimize these consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Bakri et al (10) showed that depression, anxiety and stress are prevalent in SC patients compared with healthy subjects. Sogutlu et al (18) also showed that 60% and 37.5% of patients with SCD experience significant anxiety and depression, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed emotional, sociobehavioral, and cognitive progress contribute significantly to impaired psychosocial functioning, altered intraand interpersonal relationships, and reduced quality of life. 44 This arrested psychosocial development can continue into adulthood and it has been shown that behavioral and adaptive function becomes poorer with older age. 45 Specifically, those with chronic diseases such as SCD have been shown to have higher rates of both depression and anxiety, 44 which have the potential to be overlooked in those with SCD due to frequent hospitalizations and crises.…”
Section: Disease Experiencementioning
confidence: 99%
“…44 This arrested psychosocial development can continue into adulthood and it has been shown that behavioral and adaptive function becomes poorer with older age. 45 Specifically, those with chronic diseases such as SCD have been shown to have higher rates of both depression and anxiety, 44 which have the potential to be overlooked in those with SCD due to frequent hospitalizations and crises. Anxiety and depression can worsen the perception of pain, and uncontrolled pain can exacerbate these comorbidities.…”
Section: Disease Experiencementioning
confidence: 99%